2011
DOI: 10.1177/1741826711418931
|View full text |Cite
|
Sign up to set email alerts
|

Blunted local but preserved remote vascular responses after resistance exercise in chronic heart failure

Abstract: Patients with CHF present blunted vascular responses in the exercised areas, but remote vascular reactivity responses are similar to those observed in healthy individuals, suggesting that resistance exercise may remotely contribute to vascular adaptation in nontrained vasculatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
4
1
Order By: Relevance
“…Previous studies show that a typical exercise session for CHF patients lasts 60 min, which is divided into 40 min of aerobic exercise, 15 min of resistance exercise and 5-10 min of stretching [3,14,26]. The answer to the conflict between our findings and other studies [16] may be due to the patient's clinical and physical characteristics. Peak VO 2 and ejection fraction are lower in our patients, which implies that we are dealing with sicker patients.…”
Section: Mice Hiiecontrasting
confidence: 80%
See 2 more Smart Citations
“…Previous studies show that a typical exercise session for CHF patients lasts 60 min, which is divided into 40 min of aerobic exercise, 15 min of resistance exercise and 5-10 min of stretching [3,14,26]. The answer to the conflict between our findings and other studies [16] may be due to the patient's clinical and physical characteristics. Peak VO 2 and ejection fraction are lower in our patients, which implies that we are dealing with sicker patients.…”
Section: Mice Hiiecontrasting
confidence: 80%
“…Note that neither MICE nor HIIE caused significant changes in FBF and FVC. Previous studies demonstrated that an acute bout of exercise increased muscle blood flow in healthy individuals [18] and heart failure patients [16]. Thus, increase in FBF should be expected in our study.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Although there is no previous publication concerning subacute effect of an exercise session on endothelial function in patients with HFpEF, previous studies have evaluated patients with heart failure with reduced ejection fraction in a similar context. 35 , 36 Those participants responded to a single cycling exercise session with improved forearm endothelium-dependent vasodilation (reactive hyperemia) evaluated by plethysmography up to 30 minutes after exercise. 35 Currie et al 20 evaluated coronary artery disease patients after one single HIIT session and found an increase in the endothelial function after 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise effects on BF and RH seem to be systemically mediated, since a previous study with healthy subjects and chronic heart failure patients showed an increase in BF and RH measured in the forearm after resistance leg exercise (Guindani et al 2012). In addition, in healthy subjects, BF also increased after exercise performed with the muscles where BF was measured (Guindani et al 2012;Willoughby et al 2011). However, as patients with PAD presented BF and RH impairment during exercise with affected limb, responses should be different in these patients if only lower-limb exercises were employed, which should be tested in the future.…”
Section: Peripheral Vasodilatadormentioning
confidence: 91%